2023
DOI: 10.1002/spe.3263
|View full text |Cite
|
Sign up to set email alerts
|

Migrating monolithic applications to function as a service

Hendrik M. Würz,
Michel Krämer,
Marvin Kaster
et al.

Abstract: SummaryFunction as a service (FaaS) promises low operating costs, reduced complexity, and good application performance. However, it is still an open question how to migrate monolithic applications to FaaS. In this paper, we present a guideline for software designers to split monolithic applications into smaller functions that can be executed in a FaaS environment. This enables independent scaling of individual parts of the application. Our approach consists of three steps: We first identify the main tasks (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The proposed method employs a two-stage refactoring strategy, initially performing a coarse-grained decomposition followed by a fine-grained one. This approach streamlines the decomposition process into smaller, more manageable steps, providing adaptability to generate a solution at either the microservice or function level.In the fourth paper, Würz et al 4 identified the principal tasks and subtasks of the application for the purpose of partitioning. Subsequently, they outlined the program flow to ascertain which application tasks could be transformed into functions and elucidated their interdependencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method employs a two-stage refactoring strategy, initially performing a coarse-grained decomposition followed by a fine-grained one. This approach streamlines the decomposition process into smaller, more manageable steps, providing adaptability to generate a solution at either the microservice or function level.In the fourth paper, Würz et al 4 identified the principal tasks and subtasks of the application for the purpose of partitioning. Subsequently, they outlined the program flow to ascertain which application tasks could be transformed into functions and elucidated their interdependencies.…”
mentioning
confidence: 99%
“…In the fourth paper, Würz et al 4 identified the principal tasks and subtasks of the application for the purpose of partitioning. Subsequently, they outlined the program flow to ascertain which application tasks could be transformed into functions and elucidated their interdependencies.…”
mentioning
confidence: 99%